EVALUATION OF INTRODUCED STRAWBERRY VARIETIES FOR BREEDING AND PRACTICAL USE - S. F. Loginova; G. P. Atroschenko (Труды по прикладной ботанике, генетике и селекции)
The results of years of researching 85 strawberry varieties in the North-West of Russia are presented. Evaluation of introduced varieties was made as compared with the local commercial cultivars, and the sources of major biological and agronomic traits interesting for breeding and and practice were identified.